2015
DOI: 10.1016/j.jconhyd.2015.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Integrating NZVI and carbon substrates in a non-pumping reactive wells array for the remediation of a nitrate contaminated aquifer

Abstract: The work explores the efficacy of a biochemical remediation of a nitrate-contaminated aquifer by a combination of nanoscale zero-valent iron (NZVI) and bacteria supported by carbon substrates. Nitrate removal was first assessed in batch tests, and then in a laboratory bench-scale aquifer model (60cm length×40cm width×50cm height), in which a background flow was maintained. Water and natural sandy material of a stratified aquifer were used in the tests to enhance the reliability of the results. An array of non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…The combined use of ZVI and a carbon substrate for in situ biochemical denitrification has been considered in recent years and has been shown to be effective at the laboratory scale in improving denitrification rates (Della Rocca et al, 2006;Della Rocca et al, 2007). Huang et al (2015) and Hosseini and Tosco (2015) demonstrated the efficacy of nitrate removal from contaminated groundwater by a combination of ZVI and carbon substrates (pine bark, beech sawdust and maize cobs) in laboratory tests. Liu et al (2013) demonstrated that the main role of ZVI in two-layer permeable reactive barriers consisting of ZVI and activated carbon immobilizing denitrifying microbial consortia was as an oxygen capturing reagent and not for direct nitrate reduction.…”
Section: Introductionmentioning
confidence: 99%
“…The combined use of ZVI and a carbon substrate for in situ biochemical denitrification has been considered in recent years and has been shown to be effective at the laboratory scale in improving denitrification rates (Della Rocca et al, 2006;Della Rocca et al, 2007). Huang et al (2015) and Hosseini and Tosco (2015) demonstrated the efficacy of nitrate removal from contaminated groundwater by a combination of ZVI and carbon substrates (pine bark, beech sawdust and maize cobs) in laboratory tests. Liu et al (2013) demonstrated that the main role of ZVI in two-layer permeable reactive barriers consisting of ZVI and activated carbon immobilizing denitrifying microbial consortia was as an oxygen capturing reagent and not for direct nitrate reduction.…”
Section: Introductionmentioning
confidence: 99%
“…A particular case refers to the so-called daylighting, the incident in which renegade particles emerge to the surface along preferential flow paths, for instance through fractures developed by non-intended fracking. Fracking results from pressure building up during the NP injections due to continuous injections performed at high pressure (Hosseini & Tosco 2015;Luna et al 2015), as well as from clogging of the pore space following aggregation and sedimentation of the injected particles (e.g. Tosco & Sethi 2010) enhanced by slow injections (e.g.…”
mentioning
confidence: 99%
“…Pu et al [13] also report that the efficiency of nitrate removal by promoting electron migration from nZVI surface to rGO surface is enhanced. Up to now, supported nZVI materials such as goethite [14], diatomite [15], chelating resin [16,17], C [4,18], active carbon [19], biochar [20], silicon [21], graphene [22] have been studied. But these carriers still exist the disadvantages of tedious preparation and high cost.…”
Section: Introductionmentioning
confidence: 99%